The role of single nucleotide polymorphism (SNP) of DNA repair gene by recombination RAD51, XRCC2, XRCC3 and XRCC4 in postmenopausal breast cancer women - Sobczuk, Anna; Smolarz, Beata; Romanowicz-Makowska, Hanna; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2009)
Damages in human DNA can be induced by exposure to a variety of substances occurring in external environment or inside the cell. The greatest source of damages is from endogenous processes, notably spontaneous errors in DNA replication. During an average human lifetime 1017 cell division can be estimated to take place and each of them requires the incorporation of 6 × 109 nucleotides. In an average lifetime there are 6 × 1026 occasions, following only from the replication, to make an error, which can give rise to a mutation. Many other endogenous processes as well as a variety of physical factors, chemical substances and biological elements in the external environment can be a source of DNA lesions. The high frequency of alteration in DNA would have lethal consequences for organism if not checked by the DNA-repair systems.